Design for Subjective Wellbeing: Towards a Design Framework for Constructing Narrative. (28th July 2017) - Jordan, Patrick W.; Bardill, Andy; Herd, Kate; Grimaldi, Silvia
Abstract: We explore the role that interaction with products and services can play in the narratives that we develop about ourselves. We propose a four-level model, which seeks to explain this and use it as the basis for analyzing eight immersion studies. In each, we investigate the role that products and services play in shaping narratives, which in turn reflect our self-identity. We also look at archetypes – the various ideals that we can have about ourselves – and at how the alignment of narratives with these enhances our wellbeing. The model offers the potential to link narrative to design features and to identify new market opportunities. However, we recognize there may be challenges in enabling people to articulate narrative and identify their ideal archetype.